Culture clash : an international legal perspective on ethnic discrimination - Cotter, Anne-Marie Mooney (Ashgate Pub., 2011)
This book provides readers with a better understanding of the issue of ethnic discrimination and inequality. It aims to increase the likelihood of achieving equality at both the national and international levels for those suffering ethnic discrimination a.